THE EFFECT OF SWEDISH FOOT MASSAGE THERAPY ON BLOOD PRESSURE REDUCTION IN HYPERTENSION PATIENTS - suhari suhari; Mohammad Gagan Sukmantoaji; Widya Addiarto (STIKes Kepanjen, 2022)
Introduction: Hypertension is a condition in which there is a continuous increase in systolic and diastolic blood pressure 140/90 mmHg. Hypertension is a major risk factor for cardiovascular disease such as myocardial infarction, stroke and complications. Hypertension can be treated pharmacologically and non-pharmacologically. Non-pharmacological treatment for hypertensive patients is Swedish foot massage therapy. Result: The results of data analysis using the Mann Whitney test showed that the significant difference between the intervention group and the control group was p 0.002. Therefore, it can be concluded that Swedish foot massage therapy has an effect on reducing blood pressure in hypertensive patients. Future studies should conduct research on Swedish foot massage using a larger sample and a longer timeMethod : This study used a quasi-experimental design with a two group pre-post design method. The sample consisted of 20 respondents obtained from simple random sampling. The sample was divided into two groups (10 respondents as the treatment group and 10 respondents as the control group). The treatment group was given an intervention during 3 days in a row for 15 minutes. Data analysis of this study used the T-dependent, T-independent, Wilcoxon and Mann Whitney tests.Conclusion: This study used a quasi-experimental design with a two group pre-post design method. The sample consisted of 20 respondents obtained from simple random sampling. The sample was divided into two groups (10 respondents as the treatment group and 10 respondents as the control group). The treatment group was given an intervention during 3 days in a row for 15 minutes. Data analysis of this study used the T-dependent, T-independent, Wilcoxon and Mann Whitney tests.